Quality of Intermodal Public Transportation Services as a Tool of Economic Efficiency in East Lombok Regency - Fiardi, Andi; Sulfi, Daan; Fuady, Ian; Suradika, Agus; Andriansyah , Andriansyah (Pencerah, 2025)
Public transportation supports community mobility and drives economic growth, especially in tourist areas like the East Lombok Regency. This study discusses how the quality of intermodal public transportation services contributes to economic efficiency in the area. Using a descriptive quantitative approach, this study collected data from 109 respondents who used DAMRI intermodal public transportation through a Likert scale-based survey and analyzed using the Weigh Means Score (WMS) method. The study results showed that intermodal public transportation services in East Lombok Regency were rated